Corporate financial analysis : a comprehensive beginner's guide to analyzing corporate financial risk, statements, data ratios, and reports - Robertson, Blaine ([Place of publication not identifed] : [publisher not identified], 2019)
In a digital world like this, there is need for individual investors or firms who have interest in small business and even large ones to study the evaluating target companies$1 (Bfinancial information by examining the past and current financial statements which includes balance sheet, income statements, cash flow statements. Potential investors would definitely want to form opinions about investment value and expectations for future performance. Furthermore, there are needs for financial analysis especially for small-business owners because they need to weight the effect of certain decisions like borrowing, giving out loans and even mergers. Introductory knowledge into the world of financial analysis and even up to the intermediate and professional levels are embedded in this piece.s
Chapter 1. What is financial Analysis -- Chapter 2. Components of Financial Analysis -- Chapter 3. Financial statement analysis -- Chapter 4. The Comprehensive Income Reporting -- Chapter 5. The Balance sheet -- Chapter 6. Comparing Analysis and interpretation -- Chapter 7. Context of financial analysis -- Chapter 8. Analyzing Corporate Financial Risk -- Chapter 9. Financial Ratio Analysis -- Chapter 10. Business Valuation -- Conclusion.
Corporate financial analysis :, Corporate
Keywords: CORPORATE FINANCE